Education And Socialization of Processing Egg Shells Into Organic Fertilizer As an Ecopreneurship Efforts - Kamarudin, Anna Permatasari; Erita , Erita; Nikmah , Askura; Susanti, Zulida; Fibriana, Rahmi; Jaya, Hanipan Iwan; Sukanto, Sukanto; Putri, Septina Maulia; Jalil, Abd.; Asri , Rahmadi (Education and Talent Development Center of Indonesia, 2025)
Organic waste such as egg shells is one of the environmental problems. Piling and mixed waste conditions will cause air and soil pollution. The purpose of this Community Service is to provide education on the use of egg shells, handling organic waste that can be used as fertilizer and ecopreneurship to the community in Mendale Village, Central Aceh. The number of partners who attended was 20 people consisting of mothers, the general public and village officials. The Community Service method used was in the form of counseling and demonstrations of processing egg shell waste into organic fertilizer. To measure the level of knowledge of partners, Pre-Test and Post-Test Forms were used. Meanwhile, to assess the success of the event, an evaluation form was used. The results of the increase in knowledge from the Pre-Test and Post-Test showed that partners had experienced an increase in knowledge on statements about benefits and new partners learned that egg shells can be eaten, and egg shells have added value, each 100%. After the implementation of the activity, partners learned that egg shells can be processed into organic fertilizer that can be used by them on plantation land and can increase income if it is run as an environmentally friendly business or called ecopreneurship. The evaluation conducted by partners on the implementation showed that partners felt very much in agreement with the program being held. Several statements that gave the highest 'Strongly Agree' score were regarding the appropriate theme, complete and sequential or gradual material, each 100%. Partners participated in the event enthusiastically. Further training is needed on financial management and marketing of organic fertilizers produced for optimal results